The Management of Inclusive Early Childhood Education: A Literature Review on Strategies and Evaluation in Various Countries - Sofwanudin, Wawan; Boeriswati, Endry; Arbah, Fakhrudin (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v9i1.3161, 2024)
The management of early childhood education (ECE) is a crucial aspect of child development that requires serious attention to enhance the quality of inclusive education. This article aims to present a literature review on various aspects of ECE management from different countries, focusing on policies, evaluation, and management that support inclusivity. The study examines literature on policy implementation in Kenya, the effectiveness of ECE experiences in Australia, and various studies from Indonesia that evaluate holistic, inclusive education models and ECE management. The research methodology includes an in-depth review of relevant sources to identify key themes, challenges faced in ECE management, and how inclusivity is applied in policy and practice contexts. The findings indicate the importance of effective policies, standards-based management, and systematic and inclusive evaluation to improve the quality of early childhood education for all children. The discussion addresses the challenges encountered in implementing inclusive policies, the need for innovation in management, and recommendations for improvements that consider the diversity and special needs of children. In conclusion, effective ECE management requires a holistic, integrative, and inclusive approach, strong policy support, and continuous evaluation to ensure optimal education quality for all children, without exception.